Factors Affecting the Incidence of Low Back Pain among Dairy Farmers - Putri, Ade Restina; Purwito, Dedy (Faletehan Health Journal, 2022)
Low back pain is a common problem among workers including dairy farmers. Repetitive movements in a long time accompanied with non-ergonomic positions are one of the causes of low back pain (LBP). The purpose of this study was to determine the factors that influence on the incidence of LBP among dairy farmers. The research method was descriptive analytical with a cross-sectional approach. A total of 45 workers participated in filling out the start back screening toll questionnaire, while the researchers used the Rapid Entire Body Assistance to measure their work position. The results showed 27 workers (60%) were at high risk for low back pain and 18 workers (40%) were at moderate risk. Age (0.021), physical activity (0.0001), duration of work (0.0001) and years of service (0.0001) were factors correlating to LBP incidence. Muscle stretching, ergonomic work positions, rest between activities can prevent or reduce LBP pain among dairy workers.